Architecting Angular Applications with Redux, RxJS, and NgRx : Learn to build Redux style high-performing applications with Angular 6. - Noring, Christoffer (Packt Publishing, 2018)
Managing the state of large-scale web applications is a highly challenging task with the need to align different components, backends, and web workers harmoniously. When it comes to Angular, you can use NgRx, which combines the simplicity of Redux with the reactive programming power of RxJS to build your application architecture, making your ...